Thermal Relationship in Tropical Anurans from Two Contrasting Habitats Along an Elevation Gradient in Colombia - Katalina Gutiérrez Hernández; Carlos Alberto Galindo Martínez; Jorge Luis Turriago González; Manuel Hernando Bernal Bautista (Tropical Life Sciences Research, 2024)
Anurans are ectothermic organisms highly susceptible to variations in the environmental temperature that changes with elevation and between habitats in tropical mountains. The aim of this study was to evaluate the variation of body temperature (BT) of nocturnal anurans from two contrasting habitats (open and forest habitats) along an elevation gradient in Colombia. We measured the environmental temperatures (substrate and air) and BT of 135 adult frogs of 11 species from open and forest habitats at three elevational zones of an Andean Mountain. The BT had a positive and significant relationship with environmental temperatures and showed a higher thermal dependence for substrate than air temperature, which suggests that anurans are thermoconformers and potentially tigmotherms. Additionally, BT of anurans from both habitats decreased with the elevation, but species from open habitats had a higher BT than forest species. Therefore, the impact of environmental temperatures on anurans that live at a similar altitude level is not the same, as the type of habitat has a strong influence on their BT. This information is important to a better understanding of anuran thermal biology, refine conservation strategies, and to improve the predictive power of environmental data in forecasting the effects of climate change on small ectotherms such as amphibians.